RAS gene polymorphisms, classical risk factors and the advent of coronary artery disease in the Portuguese population - Freitas, Ana I. (2008)
Background: Several polymorphisms within the renin-angiotensin system cluster of genes have been associated with the advent of coronary artery disease (CAD) or related pathologies. We investigated the distribution of 5 of these polymorphisms in order to find any association with CAD development and distinguish if any of the biochemical and behavioural factors interact with genetic polymorphisms in the advent of the disease. Methods: ACE I/D (rs4340), ACE A11860G (rs4343), AT1R A1166C (rs5186), AGT T174M (rs4762) and AGT M235T (rs699) gene polymorphisms were PCR-RFLP analysed in 298 CAD patients and 510 controls from Portugal. Several biochemical and behavioural markers were obtained. Results: ACEI/D DD and ACE11860 GG genotypes are risk factors for CAD in this population. The simultaneous presence of ACE I/D I and ACE11860 A alleles corresponds to a significant trend towards a decrease in CAD incidence. We found several synergistic effects between the studied polymorphisms and classical risk factors such as hypertension, obesity, diabetes and dyslipidaemia: the presence of the DD genotype of ACE I/D (and also ACE11860 GG) increases the odds of developing CAD when associated to each one of these classical risk factors, particularly when considering the male and early onset CAD subgroup analysis; AGT235 TT also increases the CAD risk in the presence of hypertension and dyslipidaemia, and AT1R1166 interacts positively with hypertension, smoking and obesity. Conclusion: ACE polymorphisms were shown to play a major role in individual susceptibility to develop CAD. There is also a clear interaction between RAS predisposing genes and some biochemical/ environmental risk factors in CAD onset, demonstrating a significant enhancement of classical markers particularly by ACE I/D and ACE11860.